Analisis Tingkat Pelayanan Jalan terhadap Penggunaan Lahan Koridor Kawasan Perkotaan Majene - Nur Zahrah Afifah; Reza Reski; Selvida Rara; Sima (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. The growth of urban activity in Majene Regency has a significant impact on the increase in the number of vehicles passing through main roads that function as city arteries and national roads. The imbalance between road capacity and land use intensity has the potential to reduce road service performance. This study focuses on a comprehensive analysis of Road Service Levels and tests their specific correlation with land use dominance along urban corridors. The methodology used is descriptive quantitative, involving the acquisition of primary data through traffic volume surveys, geometric characteristics, and land use patterns. The 2023 Indonesian Road Capacity Guidelines (PKJI) were used as a reference framework for calculating the V/C Ratio and LOS classification. The results of the analysis indicate that the dominance of trade and service functions on Sudirman, Hasanuddin, and Gatot Subroto Roads resulted in a LOS C value, which indicates that traffic flow is becoming saturated due to economic activities, higher education, and the influence of side obstacles. Conversely, Ahmad Yani Road, which is dominated by residential areas, has a LOS B, indicating that traffic flow is unhindered and efficient. These findings confirm that an increase in commercial activity intensity reduces road performance. Therefore, the integration of spatial planning and traffic management is necessary to maintain the efficiency of the Majene Regency urban road network in the future. Abstrak. Pertumbuhan aktivitas perkotaan di Kabupaten Majene berdampak langsung pada peningkatan jumlah kendaraan yang melalui jalan utama yang berfungsi sebagai jalan arteri kota dan jalan nasional. Ketidakseimbangan antara kapasitas jalan dan intensitas penggunaan lahan berpotensi menurunkan kinerja pelayanan jalan. Penelitian ini berfokus pada analisis komprehensif terhadap Tingkat Pelayanan Jalan serta menguji korelasi spesifiknya dengan dominasi fungsi lahan di sepanjang koridor perkotaan. Metode yang digunakan adalah kuantitatif deskriptif, melibatkan akuisisi data primer melalui survei volume lalu lintas, karakteristik geometrik, dan pola penggunaan lahan. Pedoman Kapasitas Jalan Indonesia (PKJI) 2023 digunakan sebagai kerangka acuan untuk menghitung V/C Ratio dan klasifikasi LOS. Hasil analisis mengindikasikan bahwa dominasi fungsi perdagangan dan jasa pada Jalan Sudirman, Hasanuddin, dan Gatot Subroto menghasilkan nilai LOS C yang menandakan arus lalu lintas mulai jenuh akibat aktivitas ekonomi, pendidikan tinggi, dan pengaruh hambatan samping. Sebaliknya, jalan Ahmad Yani yang di dominasi permukiman memiliki LOS B, menandakan arus lalu lintas tidak terhambat dan efisien. Temuan ini mengonfirmasi bahwa peningkatan intensitas aktivitas komersial menurunkan kinerja jalan. Oleh karena itu, integrasi perencanaan tata ruang dan manajemen lalu lintas diperlukan untuk menjaga efisiensi jaringan jalan perkotaan Kabupaten Majene kedepannya.